Josephson current in d-wave superconductor junctions with ferromagnetic insulator - Yan-Hua Liao; Meng Yang; Chang Ma; Yu-Bin Cao (Физика низких температур, 2012)
We investigate the temperature dependence of the critical current and current-phase relation by taking into
account the ferromagnetic scattering effect at interface in a d-wave superconductor (S)/ferromagnetic insulator
layer (FI)/d-wave superconductor (S) junction. It is shown that both the barrier scattering and the roughness scattering
at the interface always suppress the Andreev reflection. The Josephson critical currents depend to a great
extent on the effective exchange field of the interface and the crystal orientation of the d-wave superconductor.
The exchange field can lead to the change of the junction from 0 to π states and the alteration of the oscillation
periods. It can also enhance the Josephson critical current in the junction under certain conditions.